Pyrazolo-triazolo-pyrimidines as adenosine receptor antagonists: A complete structure–activity profile - Cacciari, Barbara (Kluwer Academic Publishers, 2006)
In the last 5 years, many efforts have been conducted searching potent and selective human A(3) adenosine antagonists. In this field several different classes of compounds, possessing very good affinity (nM range) and with a broad range of selectivity, have been proposed. Recently, our group synthesized a new series of pyrazolo-triazolo-pyrimidines bearing different substitutions at the N(5) and N(8) positions, which have been described as highly potent and selective human A(3) adenosine receptor antagonists. The present review summarizes available data and provides an overview of the structure–activity relationships found for this class of human A(3) adenosine receptor antagonists.